2014
DOI: 10.1128/jcm.02460-13
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of BioPlex 2200 HIV Ag-Ab, an Automated Screening Method Providing Discrete Detection of HIV-1 p24 Antigen, HIV-1 Antibody, and HIV-2 Antibody

Abstract: bEarly and accurate diagnosis is essential for optimal therapeutic outcomes in patients infected with HIV. Currently, none of the commercially available fourth-generation assays differentiate HIV-1 and HIV-2 antibodies (Ab) or the HIV-1 p24 antigen (Ag). The aim of this study was to evaluate the performance of a novel assay, the BioPlex 2200 HIV Ag-Ab. This assay uses a multiplex flow immunoassay design allowing the simultaneous detection and identification of antibodies to HIV-1 (groups M and O), HIV-2, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 20 publications
(19 reference statements)
1
23
0
Order By: Relevance
“…In our study, we recorded 6 false-positive results: 3 in samples from subset A (prospective) and 3 in samples from subset C (screen positive only). The specificity of Liaison XL Murex HIV Ab/Ag was 99.2% in the prospective and confirmed positive populations (98.5% when samples from subset C were included), i.e., similar to that reported by Salmona et al (99.5%) (16).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In our study, we recorded 6 false-positive results: 3 in samples from subset A (prospective) and 3 in samples from subset C (screen positive only). The specificity of Liaison XL Murex HIV Ab/Ag was 99.2% in the prospective and confirmed positive populations (98.5% when samples from subset C were included), i.e., similar to that reported by Salmona et al (99.5%) (16).…”
Section: Discussionsupporting
confidence: 87%
“…Salmona et al (16) recently evaluated the BioPlex 220 assay, which also separately detects antibody and antigen. The sensitivity of the BioPlex 2200 was also 100%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specimens reactive only for the p24 antigen do not need an antibody confirming procedure, and specimens reactive only for antibody do not require an antigen confirmatory procedure. Salmona et al evaluated the BioPlex fifth-generation assay and found 100% sensitivity and 99.5% specificity in a study of 1,505 patients (16). As of January 2016, the CDC has not published a fifth-generation testing algorithm.…”
mentioning
confidence: 99%